Chelonodontops bengalensis Habib et al. 2018, a junior synonym of Tetrodon patoca Hamilton 1822, with a type species designation for Chelonodon Müller 1841 - Britz, Ralf; Tan, Heok Hui; Rüber, Lukas (Zootaxa, 2024)
A comparison of the recent description of Chelonodontops bengalensis Habib, Neogi, Og, Lee & Kim 2018 with that of Tetrodon patoca Hamilton 1822 reveals that the former is a junior synonym of the latter. Chelonodon patoca appears to be restricted in its distribution to coastal brackish waters at the mouth of the Ganges/Brahmaputra/Meghna system in India and Bangladesh and further south to at least the mouth of the Mahanadi. The valid name for the widespread Indo-Pacific species previously confused with C. patoca is C. kappa Hamilton 1822. We show that Bleeker (1850), not Rüppell (1852), was the first author to include pufferfish species in the genus Chelonodon Müller 1841, and as first revisers we choose Tetrodon kappa Hamilton 1822 as the type species of Chelonodon.